Biosensors based on nanomaterials and nanodevices - Li, Jun, 1966 May 21-; Wu, Nianqiang (Boca Raton, Fl. : CRC Press, 2014)
'This book is a useful source for readers--beginners to expert researchers--to get a quick overview of exciting potentials and critical challenges of emerging biosensors based on nanomaterials and nanodevices for future health monitoring, disease diagnosis, and therapeutic treatments. The book highlights developments in biosensors based on nanomaterials and nanodevices in about 10 to 15 chapters on focused topics. It is intended to serve as a comprehensive source for researchers, graduate students, and industrial engineers in this area, with the emphasis on the unique signal transducing mechanisms and potential applications of nanoscale biosensors'--
Includes bibliographical references and index.
Keywords: Biosensors -- Materials; Nanostructured materials